Supporting the 21st Century Classroom: Fostering Relevance and Resilience with Project-Based Learning Curricula - Shari Childers; Kara Fulton (Academic Chairpersons Conference Proceedings, 2023)
Participants will learn about building and supporting project-based learning (PBL), a scalable, flexible approach to classes and programs that cultivates 21st century competencies in students, including collaboration and resilience. They will re-imagine a course or a program at their own institution from within a PBL context.
Keywords: project-based learning; high-impact practices; integrated curriculum; transferrable skills; multidisciplinary; collaborative teaching; collaborative learning